2000
DOI: 10.1002/1520-6378(2001)26:1+<::aid-col50>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of colour categorization

Abstract: The following research elaborates on understanding and modeling the colour categorization process. The structure of colour categories is argued to resemble the structure of the distribution of colours in the perceived world. This distribution can be represented as colour statistics in some perceptual and approximately uniform colour space (e.g., the CIELUV colour space). The process of colour categorization can be modeled through the grouping of colour statistics by clustering algorithms (e.g., K-means) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 10 publications
1
22
1
Order By: Relevance
“…A natural possibility is that communicative need may be shaped largely by the statistics of colors in the world (e.g. Yendrikhovskij, 2001;Gibson et al, 2017). If this is the case, then a prior derived from the distribution of colors in the environment should provide a good account of color naming.…”
Section: Visual Environmentmentioning
confidence: 99%
“…A natural possibility is that communicative need may be shaped largely by the statistics of colors in the world (e.g. Yendrikhovskij, 2001;Gibson et al, 2017). If this is the case, then a prior derived from the distribution of colors in the environment should provide a good account of color naming.…”
Section: Visual Environmentmentioning
confidence: 99%
“…It is claimed that these distributions limit the number of possible configurations of the colour category systems. Yendrikhovskij (2001) presented computational simulations that support this view. He demonstrated how the distribution of colours in natural images can be used to extract colour categories that resemble human colour categories.…”
Section: Impact Of Environment On Similarity To Natural Systemsmentioning
confidence: 83%
“…Ever since Berlin & Kay (1969) observed that colour categories show a remarkable cross-cultural similarity, there has been an ongoing debate on what the main cause of this universal character of colour categories might be. Some authors (Van Wijk 1959;Shepard 1992;Yendrikhovskij 2001) claim that this cross-cultural similarity is due to the shared environment in which individuals use their colour categories. These environments exhibit statistical distributions by which colours occur, which are not uniform.…”
Section: Impact Of Environment On Similarity To Natural Systemsmentioning
confidence: 99%
“…Figure 12 shows the iterative process that generates clusters and centroids. We can note that the K-means clustering analysis was performed in the field of computational modeling of color categorization 28 and data mining for systematic classification of urban form characteristics. 29 A cluster can be assimilated to the collection of individuals based on their affiliations to a type.…”
Section: Development Of a Parametric Color Typologymentioning
confidence: 99%